Enamel microstructure evolution in anthracotheres (Mammalia, Cetartiodactyla) and new insights on hippopotamoid phylogeny. (9th June 2014) - Alloing‐Séguier, Léanie; Lihoreau, Fabrice; Boisserie, Jean‐Renaud; Charruault, Anne‐Lise; Orliac, Maeva; Tabuce, Rodolphe
<x xml:space="preserve">Abstract</x> Investigations on enamel microstructure provided new data for the debate on hippopotamid origin. Observations indicated a diversity of patterns relevant to phylogenetic inferences. Within Hippopotamoidea, the distribution of these patterns seems to be in favour of a hippopotamid origin within the Palaeogene African anthracotheres. Enamel microcharacters therefore prove to be particularly relevant for future phylogenetic analysis of the superfamily, and have implications for our understanding of ecological transitions within hippopotamoids at the end of the Miocene. Indeed, unlike equids or bovids, which developed grass feeding thanks to their hypsodont molars, hippopotamoids may have had another way to exploit this resource. The combination of inter‐row sheets, which appeared early in the evolutionary history of the group, and the increased thickness of radial enamel could have eased the consumption of highly abrasive graminoids. © 2014 The Linnean Society of London